The impacts of leadership in the quality of municipal public services: case study of a portuguese municipal council - Orlando Manuel Martins Marques de Lima Rua (Management Letters/Cuadernos de Gestión, 2012)
The present research work, based on some of the components of the Common Assessment Framework, sets to analyse the influence held by leadership in specific factors that constitute the organisational climate, and also the impact that these factors have on the quality of municipal public services.For the purposes of this study, we propose Likert's exploitative autocratic and participative leadership styles to explain the genesis, structure and workflow. As far as the organisational climate is concerned, the variables used are motivation, satisfaction, empowerment, conflict and stress.The main conclusions that arose was that a participative leader confers higher relevance to the quality of service, through motivation, satisfaction, empowerment and human resources positive results, than an exploitative autocratic leader. Performed contributions are based on the empiric research hereby presented, and new research guidelines are proposed.The research methodology used was qualitative, based on the case study.